Learning Management of Early Childhood Education at Mentari Kids - Qodriyati, Tri Ulya; Raharjo, Tri Joko; Utsman, Utsman (Journal of Nonformal Education, 2018)
Statement of the problem in this study is how learning management which includes planning, implementation, and evaluation of learning in Mentari Kids Early Childhood Education, Klaten is. The aims of this study are: (a) to analyze and describe plan of learning management, (b) to analyze and describe implementation of learning management, (c) to analyze and describe evaluation of learning management of Mentari Kids Early Childhood Education, Klaten, Central Java. The approach in this research was using qualitative approach. Data collecting technique was done by using interview, observation and documentation. The subject of the research was 9 informants, which consist of 7 primary subjects, i.e 4 teachers, 1 education staff, and 2 guardians of the students. Moreover, 2 secondary subjects are the manager of the institution and principal. Validity of the data was received by the use of data triangulation and triangulation method. The results showed that the planning of curriculum learning was conducted based on top down and bottom up by considering moral and religious values, physical, linguistic, cognitive, emotional, and art. Implementation of learning is conducted based on Daily Action Plan, Weekly Action Plan, Semester Program, Annual Program which uses integrated thematic curriculum model. The learning model is centers or Beyond Centers and Circle Time includes imtaq, natural materials, art and creativity, role play, briquet, and preparation. Learning evaluation was done by observation, anecdotal recording, and portfolio. The evaluation was carried out by diagnostic, formative, summative, until placement evaluation.